Women's Empowerment From An Islamic Perspective (Analytical Study) - Khoirul Umam; Muhammad Agus Waskito (Islamic Economics Journal, 2022)
Women's empowerment, which refers to feminist thinking, is a process of awareness and capacity towards greater participation to produce equality of degrees between women and men. It is because women are considered helpless. The economic factors that characterize women's empowerment make it partial and ignore the role of women in other aspects. In Islam, women's empowerment is holistic and multidimensional and covers religious, social, political, and economic aspects. Based on this, this study aims to describe women's empowerment in Islamic perspective and economic empowerment under women's empowerment in Islam. This research is literature research with a qualitive approach. In terms of analytical methods, this study uses critical analysis methods with data collection techniques through a literature review that examines women's empowerment from an Islamic perspective and its economic empowerment. The first research results show that the model of women's empowerment in Islam is a holistic preparation of empowered women that includes four religious, social, political, and economic dimensions. It means that the empowered woman in the Islamic perspective carries out her role with full awareness, including all aspects of her role, in the aspects of creation, character, and roles in the family and society, as well as the sufficiency of fardhu 'ain science as a guide to life. Second, women's economic empowerment in the women's empowerment in Islamic perspective is an effort to make women able to maintain, manage, use property, and develop the property for the benefit of themselves, their families and society in order to realize their optimal role.